2012
DOI: 10.1155/2012/279431
|View full text |Cite
|
Sign up to set email alerts
|

Developing Targeted Health Service Interventions Using the PRECEDE-PROCEED Model: Two Australian Case Studies

Abstract: Aims and Objectives. This paper provides an overview of the applicability of the PRECEDE-PROCEED Model to the development of targeted nursing led chronic illness interventions. Background. Changing health care practice is a complex and dynamic process that requires consideration of social, political, economic, and organisational factors. An understanding of the characteristics of the target population, health professionals, and organizations plus identification of the determinants for change are also required.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
(45 reference statements)
0
35
0
Order By: Relevance
“…Three studies addressed program planning for rural palliative care services and programs; 2 were conducted in Australia and 1 in Canada. [18][19][20] The Australian studies found that palliative care had moved from being marginalized to a key component of rural health care delivery. 18,19 Blackford and Street 18 developed and evaluated the effectiveness of a model to improve advance-care planning in the community setting.…”
Section: Program Planningmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies addressed program planning for rural palliative care services and programs; 2 were conducted in Australia and 1 in Canada. [18][19][20] The Australian studies found that palliative care had moved from being marginalized to a key component of rural health care delivery. 18,19 Blackford and Street 18 developed and evaluated the effectiveness of a model to improve advance-care planning in the community setting.…”
Section: Program Planningmentioning
confidence: 99%
“…[18][19][20] The Australian studies found that palliative care had moved from being marginalized to a key component of rural health care delivery. 18,19 Blackford and Street 18 developed and evaluated the effectiveness of a model to improve advance-care planning in the community setting. Their model consisted of 5 domains: servicelevel governance, advance-care planning education, advance-care planning documentation, community engagement, and quality processes.…”
Section: Program Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…The model provides a stepwise guide to developing evidence-based interventions that meet the needs of the target group [21]. The model has been used to develop previous health interventions [22, 23]. The PRECEDE component guides the development of an intervention through the application of available research and an appropriate theoretical framework [20], and was used in the development of the BOOST-A™.…”
Section: Methodsmentioning
confidence: 99%